2010
DOI: 10.1073/pnas.1005554107
|View full text |Cite
|
Sign up to set email alerts
|

Role for mammalian target of rapamycin complex 1 signaling in neuroadaptations underlying alcohol-related disorders

Abstract: Alcohol addiction is a chronically relapsing disorder that includes certain maladaptive learning and memory. The serine and threonine kinase complex, mammalian target of rapamycin complex 1 (mTORC1), has been implicated in synaptic plasticity, learning, and memory by controlling protein translation. Here we show that administration of alcohol and excessive voluntary consumption of alcohol induce the activation of the mTORC1-mediated signaling pathway in the nucleus accumbens (NAc) of rodents. We further show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
251
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(277 citation statements)
references
References 46 publications
19
251
7
Order By: Relevance
“…These findings are highly consistent with the report of Neasta et al (2010), who showed that markers of mTORC1 activity were increased after withdrawal from alcohol. It is possible that changes in mTORC1 activity manifest on a different time scale in the NACsh versus NACc.…”
Section: Effect Of Cocaine Withdrawal On Indices Of Mtorc1 Activitysupporting
confidence: 82%
See 4 more Smart Citations
“…These findings are highly consistent with the report of Neasta et al (2010), who showed that markers of mTORC1 activity were increased after withdrawal from alcohol. It is possible that changes in mTORC1 activity manifest on a different time scale in the NACsh versus NACc.…”
Section: Effect Of Cocaine Withdrawal On Indices Of Mtorc1 Activitysupporting
confidence: 82%
“…rapamycin, we found significant reductions in indices of mTORC1 activity and GluA1 AMPARs and CAMKIIa within the NAC. The magnitude of these effects was similar to previous studies (Barak et al, 2013;Neasta et al, 2010). These findings are interesting given that dopamine D1-like agonists increase AMPAR insertion into NAC MSNs through a process involving CAMKIIa (Anderson et al, 2008;Sun et al, 2008) and that both dopamine and CAMKIIa have been shown to be important for the expression of psychostimulant sensitization and drugseeking behavior (Licata and Pierce, 2003;Loweth et al, 2008;Pierce et al, 1998).…”
Section: Intra-cerebroventricular Mtorc1 Inhibition Reduces Pr Responsupporting
confidence: 77%
See 3 more Smart Citations